Reduction of the Breeding Population of the Rook, Corvus frugilegus (Aves, Corvidae), in Ukraine: the Example of the Eastern Part of the Kyiv Region - Poluda, A. M.; Dupak, V. S.; Markova, A. O. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2023)
Since the 1980s, a significant decline in the number of breeding populations of the Rook, Corvus frugilegus Linnaeus, 1758, has been observed in many European countries. In Ukraine, this trend has been observed since the late 1990s. In 2021, the conservation status of the Rook in Europe was significantly upgraded — from “LC” (Least Concern) to “VU” (Vulnerable). The analysis of the material of surveys in 1983–1985 and 2021 on the territory of 1850 km² in Kyiv Region showed that during the 35 years, there was a catastrophic decrease in the number of nesting birds, it decreased almost 12 times, from 11,480 pairs in the 1980s to 961 pairs in 2021. In addition, the spatial structure of the distribution of colonies in relation to large arable agricultural land has changed. We suggest that the main reason for these changes is the widespread use of seed treatments with the active ingredient imidacloprid. The use of treated grains for food by birds leads to their death. Since 2018, the countries of the European Union countries have banned the use of insecticides containing imidacloprid on open land.